2013
DOI: 10.1053/j.gastro.2013.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Methylation Analysis and Epigenetic Unmasking Identify Tumor Suppressor Genes in Hepatocellular Carcinoma

Abstract: BACKGROUND & AIMS Epigenetic silencing of tumor suppressor genes contributes to the pathogenesis of hepatocellular carcinoma (HCC). To identify clinically relevant tumor suppressor genes silenced by DNA methylation in HCC, we integrated DNA methylation data from human primary HCC samples with data on up-regulation of gene expression after epigenetic unmasking. METHODS We performed genome-wide methylation analysis of 71 human HCC samples using the Illumina Human Beadchip 27K array; data were combined with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
144
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 41 publications
10
144
0
Order By: Relevance
“…For instance, Revill et al revealed sphingomyelin phosphodiesterase 3 as a potent tumor suppressor gene, which is hypermethylated in primary hepatocellular carcinoma (13). The present study aimed to determine whether changes in methylation status could affect HB by analyzing HB tissue samples and paired distant noncancerous tissues to profile differentially methylated genes in the disease.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, Revill et al revealed sphingomyelin phosphodiesterase 3 as a potent tumor suppressor gene, which is hypermethylated in primary hepatocellular carcinoma (13). The present study aimed to determine whether changes in methylation status could affect HB by analyzing HB tissue samples and paired distant noncancerous tissues to profile differentially methylated genes in the disease.…”
Section: Introductionmentioning
confidence: 94%
“…14,15 Neurofilaments have been implicated in the pathology of neurological diseases, [16][17][18] but recent data also point to a role in the pathology of cancer. [19][20][21] For example, NEFL and NEFM are both located within the 8p21 chromosome region and LOH of this region has been described in several cancers including breast cancer. [22][23][24] Furthermore, aberrant expression and methylation of neurofilament genes were recently detected in esophageal squamous cell, renal cell and hepatocellular carcinoma as well as in Ewing sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Furthermore, aberrant expression and methylation of neurofilament genes were recently detected in esophageal squamous cell, renal cell and hepatocellular carcinoma as well as in Ewing sarcoma. 19,21,25,26 In the present study we used a comprehensive approach to study the epigenetic inactivation of neurofilament genes in breast cancer and the functional significance of these events.…”
Section: Introductionmentioning
confidence: 99%
“…Wong et al (81) detected the downregulation of miRNA-223 expression levels in HCC tissues and investigated stathmin 1 (STMN1) as a downstream target. Methylation array analysis has been used to detect cancer-specific epigenetic alterations in HCC (82)(83)(84)(85)(86)(87)(88)(89)(90)(91). Shen et al (82) analyzed tumor and adjacent non-tumor tissue samples from 62 Taiwanese patients with HCC, using Illumina ® methylation arrays, and identified several genes that were hyper-or hypo-methylated in tumor tissues, as compared with adjacent non-tumor tissues (82).…”
Section: Molecular Alterations In Hcc Tumorsmentioning
confidence: 99%
“…The tumor-suppressor gene candidates were efficiently identified by detecting downregulation and methylation in tumor tissues, and without chromosomal deletion of the loci of the targeted genes. Revill et al (90) performed a genome-wide methylation array analysis of HCC samples and a microarray analysis of gene re-expression in HCC cell lines, and then combined the data to locate an epigenetically-silenced tumor-suppressor gene. These studies demonstrate that the majority of hepatocarcinogenesis studies focus on the changes in tumor tissues and the comparison of HCC cell lines or tumor tissues with adjacent normal liver tissues.…”
Section: Molecular Alterations In Hcc Tumorsmentioning
confidence: 99%